Productivity Changes in The Manufacturing Industry of East Java: An Application of the Malmquist Index Decomposition Analysis - Selamet Joko Utomo; Tripitono Adi Prabowo; Alvin Sugeng Prasetyo (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the productivity performance of East Java’s total manufacturing industry using the Malmquist Productivity Index (MPI) approach, which decomposes productivity growth into Technological Change (TECH), Technical Efficiency Change (TECCH), and Scale Efficiency Change (SECH). The results show that the Total Factor Productivity Change (TFPCH) for the overall industry is greater than one, indicating a positive growth in productivity during the study period. The increase in SECH further suggests that industries are operating closer to their optimal scale of production. The findings imply that sustained productivity improvement requires continuous innovation, investment in technology, human capital development, and stronger supply chain integration. Therefore, strengthening local input industries, enhancing industrial clusters, and promoting digital transformation are essential strategies to ensure sustainable and competitive industrial growth in East Java’s manufacturing sector.